Parameter sensitivity formulation for viscoelastic structures - Tauzowski, Piotr; Kleiber, Michał (Computer Assisted Methods in Engineering and Science, 1999)
The problem of sensitivity of viscoelastic response with respect to material parameters is studied in the paper. The direct differentiation method is employed. The FEM-related implementation issues are discussed. A number of numerical examples illustrates the theory.